1996
DOI: 10.1111/j.1751-1097.1996.tb03086.x
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Solar Radiation‐Induced Photodamage in Marine Bacterioplankton

Abstract: Abstract— There has been much recent concern about the effects of increased UV radiation at certain locations on the earth's surface. There have been extensive studies of ultraviolet radiation effects on phytoplankton and primary production, yet the effects of UVB upon bacterioplankton have been largely overlooked. Bacteria play a central role in the cycling of nutrients and energy flow to higher trophic levels, serving as both mineralizers and secondary producers that are consumed by higher organisms. We have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
90
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(104 citation statements)
references
References 50 publications
11
90
1
Order By: Relevance
“…Also, the use of Whirlpack bags with lower transmittance to UVBR in the 3 h experiments, compared to polypropylene bags as used in the diurnal experiments, might have contributed to this. Many studies report an inhibitory effect of UVBR on the leucine and thymidine incorporation rates (Bailey et al 1983, Herndl et al 1993, Aas et al 1996, Jeffrey et al 1996a, but inhibition by UVAR and PAR has also been found in olher studies. Sieraciri & Sieburth (1986) showed that UVAR was responsible for the observed growth delay of marine bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the use of Whirlpack bags with lower transmittance to UVBR in the 3 h experiments, compared to polypropylene bags as used in the diurnal experiments, might have contributed to this. Many studies report an inhibitory effect of UVBR on the leucine and thymidine incorporation rates (Bailey et al 1983, Herndl et al 1993, Aas et al 1996, Jeffrey et al 1996a, but inhibition by UVAR and PAR has also been found in olher studies. Sieraciri & Sieburth (1986) showed that UVAR was responsible for the observed growth delay of marine bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterioplankton seem to lack UV-screening pigments such as mycosporines or scytonemins, possibly because of their small size [50,51]. As a consequence, bacterioplankton are more prone to UV-B stress than larger eukaryotic organisms and exposure produces about double the amount of cyclobutane dimers as shown in a case study in the Gulf of Mexico [52,53]. This damage is at least partially offset by photoreactivation [54].…”
Section: Bacterioplankton and Picoplanktonmentioning
confidence: 96%
“…Bacterial production is inhibited by UV radiation (Herndl et al 1993, Aas et al 1996, Visser et al 1999). UV-B-induced DNA damage has been reported to be higher in small bacterioplankton cells than in larger eukaryotic plankton (Jeffrey et al 1996a) and to fluctuate in a diel pattern (Jeffrey et al 1996b). Damage was seen to accumulate during the afternoon hours but then be repaired between sunset and the following sunrise.…”
mentioning
confidence: 92%